2019
DOI: 10.1177/1747954119827192
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic for the relationship between caring coaching and elite athlete performance

Abstract: While the topic of caring coaching and its relationship to performance has been explored by researchers mainly in the UK, it has been neglected in the US with the exception of three studies by Fisher and colleagues. The core problem is a lack of understanding regarding the construct of care and whether coaches can care about athletes in pressure-filled, high-stakes, win-at-all-cost sport contexts. Thus, in this paper, we draw upon the ethic of care first proposed by Gilligan and later developed by Noddings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Specifically, reflecting on different nutritional approaches was a source of knowledge and experiencing the embodied consequences of these strategies led to changes in Additionally, practitioners described providing formal workshops and individual advice to athletes. Related to this, how practitioners care for athletes in sport contexts has received some recent attention, with authors calling for an ethic of care in high performance sport (Cronin et al, 2020;Fisher et al, 2019). In keeping with this theme, some sport nutrition practitioners articulated practices such as paying attention to and collaborating with female athletes to support their complex nutritional needs: So, we work on grams per kilo and we've got ranges for the group in terms of where we think people should be at on different days and at different phases and then that's sort of individualised based on some Importantly, data from the thematic analysis also revealed that in contrast to the other participants, three practitioners (two of whom were female) did not consider menstrual or contraceptive status to be linked to athlete nutrition or performance: I couldn't tell you off the top of my head, who was or wasn't on contraception unless I went specifically asking, the medics.…”
Section: Theme 3: a Continuing Need For Ongoing Education And Further...mentioning
confidence: 99%
“…Specifically, reflecting on different nutritional approaches was a source of knowledge and experiencing the embodied consequences of these strategies led to changes in Additionally, practitioners described providing formal workshops and individual advice to athletes. Related to this, how practitioners care for athletes in sport contexts has received some recent attention, with authors calling for an ethic of care in high performance sport (Cronin et al, 2020;Fisher et al, 2019). In keeping with this theme, some sport nutrition practitioners articulated practices such as paying attention to and collaborating with female athletes to support their complex nutritional needs: So, we work on grams per kilo and we've got ranges for the group in terms of where we think people should be at on different days and at different phases and then that's sort of individualised based on some Importantly, data from the thematic analysis also revealed that in contrast to the other participants, three practitioners (two of whom were female) did not consider menstrual or contraceptive status to be linked to athlete nutrition or performance: I couldn't tell you off the top of my head, who was or wasn't on contraception unless I went specifically asking, the medics.…”
Section: Theme 3: a Continuing Need For Ongoing Education And Further...mentioning
confidence: 99%
“…Further, caring relationships have recently been proposed as key in ensuring high performance sport is sustainable and allowing personal, educational and performance development to be pursued simultaneously (e.g., Fisher et al, 2019;Lindgren & Barker-Ruchti, 2017). While these features show clear overlap with previous research, this study is the first to also evidence links to positive personal and educational developmental outcomes within the context of elite youth soccer.…”
Section: Discussionmentioning
confidence: 62%
“…Our findings specifically support the importance of perceiving the environment as supportive with an emphasis on holistically understanding and developing athletes, as well as being characterized by a set of coherent espoused and enacted values. Further, caring relationships have recently been proposed as key in ensuring high-performance sport is sustainable and allowing personal, educational and performance development to be pursued simultaneously (e.g., Fisher et al, 2019; Lindgren & Barker-Ruchti, 2017). While these features show clear overlap with previous research, this study is the first to also evidence links to positive personal and educational developmental outcomes within the context of elite youth soccer.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are generally anxious if their children, who are young athletes and students, experience negative attitudes towards their children. The social attitude in this study can be defined as someone who has empathy, task orientation, ego orientation (Fisher et al, 2019). The results showed that the training model based on comprehensive teaching-learning had a significant effect on social attitudes at the ages of 10 and 11, while at the age of 12 the training model had an effect but it was not significant.…”
Section: Discussionmentioning
confidence: 70%